Intra- and inter-rater reliability of a video-based method to quantify stroke synchronisation in crew-boat sprint kayaking - Tay, C. S.; Kong, P. W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to assess the reliability of a method to quantify stroke synchronisation in crew-boat sprint kayaking from video analysis. One sub-elite K2 crew was recorded from a sagittal view at 120 Hz during a 200-m time trial. Video analysis identified the timing difference (termed "offset") between the front and back paddlers at four meaningful positions of the stroke (catch, immersion, extraction and release), with zero offset indicating perfect synchronisation. The anlaysis was performed twice by the same rater, as well as independently by two other raters. Results showed almost perfect intra-rater reliability, where intra-class correlation coefficients (ICC) ranged from .87 to 1.00, and standard error of measurement (SEM) from 0 to 5 milliseconds (ms). Inter-rater reliability was substantial to almost perfect (ICC .72 - .94, SEM 2 - 6 ms).